10 - ‘Gifts of Art for Kenyan (M)Pigs’: Festival of Resistance Against Elite Impunity in Kenya - Ombati, Mokua (Africa Development, 2017)
Drawing from the combined theories of Interaction Rituals and Symbolic Interactionalism, this article analyses the performance of rituals and the social construction of symbols in the mechanisms of art resistance against elite impunity in Kenya. Through ethnographic research, the study explores the unique varieties of art resistance advanced by Kenyan youth, their primacy, creativity and symbolism in the struggle for social transformation and contention, and the power of those typologies to transform both participants and the general public into more tolerant, enlightened, critical and active advocates of social change.